2022
DOI: 10.3390/su14138161
|View full text |Cite
|
Sign up to set email alerts
|

Remote Working and Home Learning: How the Italian Academic Population Dealt with Changes Due to the COVID-19 Pandemic Lockdown

Abstract: The COVID-19 pandemic introduced changes in people’s lives that affected their mental health. Our study aimed to explore the level of psychological distress in the academic population during the lockdown period and investigate its association with the new working or studying conditions. The study sample included 9364 students and 2159 employees from five Italian universities from the study IO CONTO 2020. We applied linear regression models to investigate the association between home learning or remote working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 77 publications
(102 reference statements)
3
15
2
Order By: Relevance
“…This result contradicts several reports, such as those by Beckel and Fisher (2022), Calleja and Mota (2022), Pataki-Bittó and Kun (2022) and de Sousa et al (2022), regarding the link between being female and mental issues. Macciotta et al (2022), Heiden et al (2021), Mendonça et al (2022), Pataki-Bittó and Kun (2022), Maillot et al (2022) and Niu et al (2021) found a significant relationship between having children to care for and stress. However, our findings are not an exception.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…This result contradicts several reports, such as those by Beckel and Fisher (2022), Calleja and Mota (2022), Pataki-Bittó and Kun (2022) and de Sousa et al (2022), regarding the link between being female and mental issues. Macciotta et al (2022), Heiden et al (2021), Mendonça et al (2022), Pataki-Bittó and Kun (2022), Maillot et al (2022) and Niu et al (2021) found a significant relationship between having children to care for and stress. However, our findings are not an exception.…”
Section: Discussionmentioning
confidence: 97%
“…Individual Variables 2.1.1. Sociodemographic Variables Socioeconomic factors have often been found to be relevant in explaining stress and isolation in WFH practices (Pataki-Bittó and Kun 2022;Sutarto et al 2021;Beckel and Fisher 2022;Song and Gao 2020;Mendonça et al 2022;de Sousa et al 2022;Macciotta et al 2022;Fang et al 2022). Many studies have reported that gender is a relevant variable to explain positive and negative feelings and psychological effects such as stress and isolation produced by home teleworking (Song and Gao 2020;Mendonça et al 2022).…”
Section: Sociodemographic Variablesmentioning
confidence: 99%
See 3 more Smart Citations